Disability and health in two qualitative studies: the itineraries of rehabilitation in Argentina and Chile - Venturiello, María Pía (2018)
The objective of this article is to describe the therapeutic itineraries for the care and rehabilitation of people with disabilities in Argentina and Chile. As a methodological strategy, we will present secondary data and some of the findings of two independent qualitative studies. The results show that when pursuing healthcare, people with disabilities and their families face situations that are negative for their quality of life, social participation, and self-esteem. In this way, their position of disadvantage and social devaluation is reproduced.